Wandering stars - Orange, Tommy, 1982- (New York, Alfred A. Knopf, 2024)
Colorado, 1864. Star, a young survivor of the Sand Creek Massacre, is brought to the Fort Marion Prison Castle. Wandering Stars traces the legacies of the Sand Creek Massacre of 1864 and the Carlisle Industrial School for Indians through to the shattering aftermath of Orvil Redfeather's shooting in There There.
"This is a Borzoi book"--Title page verso.
Keywords: United States Indian School (Carlisle, Pa.) -- Fiction; Indians of North America -- Fiction; Sand Creek Massacre, Colo., 1864 -- Fiction; Indians of North America -- Rites and ceremonies -- Fiction; School shootings -- Fiction; Generational trauma -- Fiction; Epigenetics -- Fiction; Historical fiction; Social problem fiction